ANALISIS SEISMOGRAM TIGA KOMPONEN TERHADAP MOMEN TENSOR GEMPA BUMI DI MANOKWARI PAPUA BARAT - Setyowidodo, Irwan; Dwi Handayani, Aprilia (Vidya Karya Jurnal Kependidikan, 2014)
This research has the objective to find out the characteristics of earthquake so that it can be used to predict the preventive action for the people around. Based on the data analysis of earthquake in Manokwari Papua Barat, earthquake in January 3 2009 had the magnitude 7.1 Mw with the epicentrum in lattitude -0.705, longitude 132.84 and 25 km for depth.The cause of eartquake is strike-slip oblique moving to southeast, northwest. Earthquake in January 6 2009 had the magnitude 5.7 Mw with the epicentrum in lattitude -0.63, longitude 133.33 and 10 kms for depth.The cause of eartquake is reverse moving to northeast, southwest. Earthquake in August 2 2009 had the magnitude 5.9 Mw with the epicentrum in lattitude -0.444, longitude 133.06 and 10 kms for depth. The cause of eartquake is reverse moving to northeast, southwest. Earthquake in January 13 2010 had the magnitude 5.7 Mw with the epicentrum in lattitude -0.72, longitude 133.33 and 42 kms for depth. The cause of eartquake is reverse moving to orthwest, southeast.